Equitable Relief Against Forfeiture - Sinnadurai, Visu (Journal of Malaysian and Comparative Law, 2019)
The past two years have been fruitful years for the court of equity. The Court have, in a number of cases over these two years asserted the right to relieve against the forfeiture of property. The Courts, not only in England, but also in Malaysia, Australia and New Zealand have thus demonstrated that 'equity has unlimited and unfettered jurisdiction to relieve against contractual forfeiture and penalties.'